2016
DOI: 10.1155/2016/4323742
|View full text |Cite
|
Sign up to set email alerts
|

Using Cosmic-Ray Neutron Probes to Monitor Landscape Scale Soil Water Content in Mixed Land Use Agricultural Systems

Abstract: With an ever-increasing demand for natural resources and the societal need to understand and predict natural disasters, soil water content (SWC) observations remain a critical variable to monitor in order to optimally allocate resources, establish early warning systems, and improve weather forecasts. However, routine agricultural production practices of soil cultivation, planting, and harvest make the operation and maintenance of direct contact point sensors for long-term monitoring challenging. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 49 publications
1
51
0
Order By: Relevance
“…The COSMIC operator [Shuttleworth et al, 2013] enables effective data assimilation for snow-free environments. As approaches to separate the signal of different hydrogen pools are emerging [Baatz et al, 2015;Baroni and Oswald, 2015;Franz et al, 2016;Heidb€ uchel et al, 2016;Tian et al, 2016], applications in other environments than open fields, including measurements of snow canopy interactions, are promising [Desilets, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…The COSMIC operator [Shuttleworth et al, 2013] enables effective data assimilation for snow-free environments. As approaches to separate the signal of different hydrogen pools are emerging [Baatz et al, 2015;Baroni and Oswald, 2015;Franz et al, 2016;Heidb€ uchel et al, 2016;Tian et al, 2016], applications in other environments than open fields, including measurements of snow canopy interactions, are promising [Desilets, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the equal weighting of independent soil moisture measurements suggested by Franz et al (2012b), improved soil moisture estimates were obtained by applying a weighting function (Schrön et al, 2017). In principle, a single calibration campaign is adequate; however, when additional pools of H are present, two or more campaigns at different soil water contents will produce better calibration (Franz et al, 2012b, 2013a, 2016; Lv et al, 2014; Iwema et al, 2015; Heidbüchel et al, 2016). Finally, an alternative calibration function for soil moisture estimation was developed by Franz et al (2013b).…”
Section: Status Of the Methodsmentioning
confidence: 99%
“…Numerous validation studies across the globe (see e.g. Bogena et al 2013;Franz et al 2015Franz et al , 2016Iwema et al 2017, among others) have shown the CRNP to have area-average measurement accuracies of less than 0.03 cm 3 cm −3 against a variety of industry standard SWC point scale probes. The calculated SWC within the measurement volume in a non-linearly weighed average with increased sensitivity near the CRNP (Schrön et al 2017).…”
Section: Hydrogeophysical Datasetsmentioning
confidence: 99%
“…Binley et al 2015;Coopersmith et al 2014;Franz et al 2016;Villarreyes et al 2011) offer promising opportunities in precision agriculture. One such instrument to be explored in this work is the cosmicray neutron probe (CRNP), which has been used within agricultural systems to approximate SWC at the field-to small-watershed-scale (Franz et al 2015).…”
Section: Introductionmentioning
confidence: 99%